First Report of Bronzing Disease Caused by Pantoea stewartii on Jackfruit in China - Zhao, Ya (Plant disease, 2023)
Jackfruit (Artocarpus heterophyllus) is an important tropical commercial fruit crop grown in Hainan province, China. In recent years, severe jackfruit bronzing disease has been found in 11 cities and counties in Hainan. On average, 80% of trees in a jackfruit orchard are affected once bronzing disease is detected. The disease is characterized by yellow-orange to reddish discoloration of the pulp and rags of infected fruit (Hernández-Morales et al. 2017). Jackfruit bronzing disease has been reported previously in the Philippines (Gapasin et al. 2012), Malaysia (Zulperi et al. 2017), and Mexico (Hernández-Morales et al. 2017). Diseased samples of jackfruit 'Tai Eight' with the bronzing symptoms were collected from a plantation in Changjiang, Hainan. The samples were sterilized with 75% ethanol for 30 s, then soaked with 1% sodium hypochlorite for 8 min, and rinsed with sterilized distilled water. The sterilized tissues were ground in 2 mL sterile water, and allowed to stand for 30 min. Then, 500 μL of the supernatant was spread on Glucose-Yeast agar medium and incubated overnight at 28ºC. Representative bacterial colonies were lemon-yellow, convex and smooth, transparent with entire edges. Colonies were Gram-negative, positive for catalase and gelatin liquefaction, which were consistent with the characteristics of P. stewartii subsp. stewartii. In PCR amplifications, an 920 bp amplicon of strain JTPE2 with the primers ES16/ESIG2c (Coplin et al. 2002) and an 1100 bp amplicon of strain JTPC2 with the primers CPSL1/CPSR2c (Ibrahim et al. 2019) were obtained, whereas no bands were observed for the negative control samples. The ES16/ESIG2c and CPSL1/CPSR2c fragments were sequenced for nucleotide BLAST (BLASTn) searches of the NCBI database and phylogenetic tree construction. The obtained ES16/ESIG2c sequences (SAR accession no. SRR22405292) showed 99.07%-99.60% similarity with P. stewartii subsp. stewartii (CP017581, AJ311838 and MF598163). The obtained CPSL1/CPSR2c sequences (SAR accession no. SRR22405293) showed 99.40%-99.99% similarity with P. stewartii subsp. stewartii (MW971422, MH752485 and MH257287). Phylogenetic analysis based on cpsDE sequences (Ibrahim et al. 2019) using the maximum likelihood method revealed that strains JTPE2 and JTPC2 were clustered together with P. stewartii subsp. stewartii. A pathogenicity test was conducted by injecting 2 mL of 108 CFU/ml bacterial suspension into pulp from healthy, surface-sterilized jackfruit. Pulp injected with sterilized distilled water served as a negative control. All inoculated samples produced bronzing symptoms from 2-3 weeks post-inoculation similar to the field-observed symptoms, whereas control fruit were asymptomatic. The strains were reisolated from symptomatic jackfruit pulp to complete Koch's postulates. The bacterial suspension was inoculated on 2-week-old maize seedlings to supplement in vivo pathogenicity testing. Typical Stewart's disease leaf symptoms were visible at 2 weeks post-inoculation. Based on morphological, biochemical, and physiological evidence, pathogenicity tests, and molecular analyses, the pathogenic bacterium isolated from 'Tai Eight' jackfruit was identified as P. stewartii subsp. stewartii. To our knowledge, this is the first report of bronzing disease caused by P. stewartii subsp. stewartii on jackfruit in China, which may assist in preventing the global spread of jackfruit bronzing disease